Using Monozygotic Twins to Dissect Common Genes in Posttraumatic Stress Disorder and Migraine - Bainomugisa, Charlotte K.; Sutherland, Heidi G.; Parker, Richard; Mcrae, Allan F.; Haupt, Larisa M.; Griffiths, Lyn R.; Heath, Andrew; Nelson, Elliot C.; Wright, Margaret J.; Hickie, Ian B.; Martin, Nicholas G.; Nyholt, Dale R.; et al. (Frontiers in Neuroscience, 2021)
Epigenetic mechanisms have been associated with genes involved in Posttraumatic stress disorder (PTSD). PTSD often co-occurs with other health conditions such as depression, cardiovascular disorder and respiratory illnesses. PTSD and migraine have previously been reported to be symptomatically positively correlated with each other, but little is known about the genes involved. The aim of this study was to understand the comorbidity between PTSD and migraine using a monozygotic twin disease discordant study design in six pairs of monozygotic twins discordant for PTSD and 15 pairs of monozygotic twins discordant for migraine. DNA from peripheral blood was run on Illumina EPIC arrays and analyzed. Multiple testing correction was performed using the Bonferroni method and 10% false discovery rate (FDR). We validated 11 candidate genes previously associated with PTSD including DOCK2, DICER1, and ADCYAP1. In the epigenome-wide scan, seven novel CpGs were significantly associated with PTSD within/near IL37, WNT3, ADNP2, HTT, SLFN11, and NQO2, with all CpGs except the IL37 CpG hypermethylated in PTSD. These results were significantly enriched for genes whose DNA methylation was previously associated with migraine (p-value = 0.036). At 10% FDR, 132 CpGs in 99 genes associated with PTSD were also associated with migraine in the migraine twin samples. Genes associated with PTSD were overrepresented in vascular smooth muscle, axon guidance and oxytocin signaling pathways, while genes associated with both PTSD and migraine were enriched for AMPK signaling and longevity regulating pathways. In conclusion, these results suggest that common genes and pathways are likely involved in PTSD and migraine, explaining at least in part the co-morbidity between the two disorders.